Web coding & development all-in-one - McFedries, Paul (--For dummies., 2018)
Speak the languages that power the web With more high-paying web development jobs opening every day, people with coding and web/app building skills are having no problems finding employment. If you & rsquo;re a would-be developer looking to gain the know-how to build the interfaces, databases, and other features that run modern websites, web apps, and mobile apps, look no further. Web Coding & Development All-in-One For Dummies is your go-to interpreter for speaking the languages that handle those tasks. Get started with a refresher on the rules of coding before diving into the languages that build interfaces, add interactivity to the web, or store and deliver data to sites. When you're ready, jump into guidance on how to put it all together to build a site or create an app. Get the lowdown on coding basics Review HTML and CSS Make sense of JavaScript, jQuery, PHP, and MySQL Create code for web and mobile apps There & rsquo;s a whole world of opportunity out there for developers & mdash;and this fast-track boot camp is here to help you acquire the skills you need to take your career to new heights!